(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To assess the outcome of Flare-up versus Antagonist protocol and to determine factors related to poor responders. Methodology: this is a random control trial among 834 patients who were predicted to ovarian poor response from 2014 to 2018. Results: The rate of biochemical pregnancy was 4.5% with Flare-up versus 8,1% with Antagonist (p<0.05). The rate of fertilization, implantation and clinical pregnancy were not significant different between the 2 protocols. Age and number of AFC were significant factors to predict poor ovarian response. However, with Flare-up, there were 2 more factors could be used for the purpose which was basal FSH and E2 day 7. Conclusion: The outcome of treatment between Flare-up and Antagonist among predicted poor ovarian response was comparable. Age and AFC were valuable factors in prediction of poor ovarian response.